Faktor-faktor Yang Mempengaruhi Harga Saham Perusahaan: Studi Kasus Pada Sub Sektor Perkebunan Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Sukartaatmadja, Iswandi; Khim, Soei; Lestari, Maulvi Novia (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Changes in stock prices fluctuations are influenced by internal factors or also called fundamental factors originating from within the company which are shown in the company's financial statements, and external factors related to the economic conditions of a country. This study aims to determine the effect of Liquidity, Profitability, Inflation, and BI7DRR on Stock Prices in Plantation Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2016-2020 Period, either simultaneously or partially. This study uses quantitative methods with panel data regression analysis using the Eviews version 9.0 program. The results of this study indicate that partially the Current Ratio (CR) variable has no and no significant effect on stock prices, Return On Assets (ROA) partially and significantly affects stock prices, Inflation partially and significantly affects stock prices, and BI7DRR partially partial has no effect and is not significant to stock prices. Simultaneously, the variables Current Ratio (CR), Return On Assets (ROA), Inflation and BI7DRR have a significant effect on stock prices in Plantation Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2016-2020 Period. Keyword : Liquidity, Profitability, Inflation, BI7DRR, Stock Prices